Economic evaluation of the CARDS study - de Portu, Simona; Menditto, Enrica; Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2006)
Introduction: cardiovascular diseases (CVD) are the major component of premature mortality, generate disability and are a relevant source of cost. The growing incidence of CVD is associated with lifestyle and other modifiable risk factors. Prevention and preclinical detection of CVD reduce morbidity and mortality. Type 2 diabetes is associated with a substantially increased risk of cardiovascular disease. Objective: the aim of the study was to evaluate the health economic consequence of medical therapy with atorvastatin for primary prevention of major cardiovascular events in patients with type 2 diabetes in Italy. Materials and method: in order to reach our objective we drew clinical information from the CARDS study. This economic evaluation was carried out conducting a cost/effectiveness analysis from the perspective of National Health Service (NHS). The analysis was applied to a time horizon in conformity with the observational period adopted in the CARDS study (3.9 years). An incremental cost/effectiveness ratio (ICER) was calculated and is expressed as cost per life years gained (LYG). In order to test the robustness of the results, a one-way sensitivity analysis was performed. Results: the total cost of atorvastatin therapy over 3.9 years amounts to around 1.5 million of euros per 1,000 patients. The total cost of adding atorvastatin to standard care in people treated for primary prevention of major cardiovascular events in type 2 diabetes as those involved in the CARDS study would entail an additional cost of about 1,2 million of euros per 1,000 patients treated per 3.9 years, with an incremental cost/effectiveness ratio (ICER) equivalent to 36,566 euros per patient per LYG. Discussion: the current study is the first economic evaluation of CARDS study to the Italian situation. The results of the current study show that hypolipemic therapy with atorvastatin 10 mg in diabetic individuals is to be considered cost effective.